2016
DOI: 10.3892/etm.2016.3496
|View full text |Cite
|
Sign up to set email alerts
|

Hospital initiatives in promoting smoking cessation: A 12-year follow-up

Abstract: Abstract. In the present study, the availability of smoking cessation programs (SCP) was surveyed in the same randomly selected USA hospitals in 2000 and 2012. A total of 102 USA hospitals were randomly selected for this survey. Each hospital website was searched for the topic of smoking cessation. In the second phase of the survey, the main switchboard number of each hospital was anonymously telephoned and the 'stop smoking clinic' was requested. The phone survey results showed that the percentage of hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(17 reference statements)
1
0
0
Order By: Relevance
“…Although most healthcare systems in the United States attempt to ascertain tobacco use status (with varying degrees of effectiveness), a minority of patients receive even advice to quit on a consistent basis, much less assistance or follow-up. 123–130 Similar results have been found specifically in surgical patients. A national survey of anesthesiologists found that although most asked their patients about tobacco use, only 30% reported advising them to quit, and 5% provided any assistance.…”
Section: Approach To Treatment In Healthcare Settingssupporting
confidence: 78%
“…Although most healthcare systems in the United States attempt to ascertain tobacco use status (with varying degrees of effectiveness), a minority of patients receive even advice to quit on a consistent basis, much less assistance or follow-up. 123–130 Similar results have been found specifically in surgical patients. A national survey of anesthesiologists found that although most asked their patients about tobacco use, only 30% reported advising them to quit, and 5% provided any assistance.…”
Section: Approach To Treatment In Healthcare Settingssupporting
confidence: 78%